ASSOCIATIVE MEANING FOUND IN PROVERBS IN BAJAWA LANGUAGE USED BY PEOPLE IN DOKA VILLAGE - Meo, Darius; Duka, Yofita L; Doi, Maksimilianus (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2022)
The aim of this study was to find out the types of associative meaning in proverbs in Bajawa language used by people in Doka village. There were five types of associative meaning, stylistic or social meaning, effective meaning, reflective meaning, and collocative meaning as stated by Leech (1981). This study used qualitative method to analyze the data. Collecting data adopted was that the writer is the main instrument by preparing the list of proverbs in Bajawa language used by people in Doka village, then, choosing some native speakers to complete the data. Data analysis was by classifying proverbs into five types of associative meaning. The analysis shows that there are four types associative meaning can be found on proverbs. Proverbs are used in different context. They are in birth context, wedding context, reba context, process of building the traditional house and death context, affective meaning found in proverbs of wedding context. The result shows that there are 103 proverbs used by people in Doka village. The writer found there are 65 proverbs in connotative meaning, 8 proverbs in stylistic or social, 25 proverbs in affective meaning and 5 proverbs in reflective meaning. Those proverbs are used in different context.